Comparison of different prediction models for the indication of implanted cardioverter defibrillator in patients with arrhythmogenic right ventricular cardiomyopathy. (23rd September 2020) - Aquaro, Giovanni Donato; De Luca, Antonio; Cappelletto, Chiara; Raimondi, Francesca; Bianco, Francesco; Botto, Nicoletta; Barison, Andrea; Romani, Simona; Lesizza, Pierluigi; Fabris, Enrico; Todiere, Giancarlo; Grigoratos, Crysanthos; et al.
Abstract: Aims: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is associated with a high risk of sudden cardiac death. Three different prediction models for the indication of implanted cardioverter defibrillator (ICD) are now available: the 5 year ARVC risk score, the International Task Force Consensus (ITFC) criteria, and the Heart Rhythm Society (HRS) criteria. We compared these three prediction models in a validation cohort of patients with definite ARVC. Methods and results: In a cohort of 140 patients with definite ARVC, the 5 year ARVC risk score and the ITFC and HRS criteria were compared for the prediction of a major combined endpoint of sudden cardiac death, appropriate ICD intervention, resuscitated cardiac arrest, and sustained ventricular tachycardia. During the follow‐up, 65 major events occurred. The 5 year ARVC risk score with a threshold >10%, derived from the maximally selected rank statistic, predicted 62 (95%) events [odds ratio (OR) 9.1, 95% confidence interval (CI) 2.6–32, P = 0.0006], the ITFC criteria 53 (81%, OR 4.8, 95% CI 2.2–10.3, P = 0.0001), and the HRS criteria 29 (45%, OR 4.2, 95% CI 1.9–9.3, P = 0.0003). At the analysis of decision curve for ICD implantation, a 5 year ARVC risk score >10% showed a greater net benefit than the ITFC and HRS criteria over a wide range of threshold probability of events. Finally, at multivariate analysis, the 5 year ARVC risk score >10% was the only independent predictor of major events. Conclusions: The 5 year score with a threshold of >10% was more effective for predicting events than the ITFC and HRS criteria.